Static And Dynamic Yield Stress Of Water-Bentonite Suspensions - C. Tsamantaki (Society for Mining, Metallurgy & Exploration, 2006)
Water-bentonite suspensions exhibit a yield stress which is defined as the minimum applied stress for flow. Considerable debate exists about the yield stress being a material property, hence different measuring methods should give similar answers, but several investigators have demonstrated that it is an engineering reality. Yield stress is normally estimated indirectly from the rheogram obtained with a viscometer following an extrapolation to zero shear rate (the dynamic yield stress), but the technique may be prone to errors because of slip flow. Direct measurements, not prone to such errors, rely on an independent assessment of the yield stress, normally carried out with the vane method (the static yield stress). In this paper results are presented and compared regarding the yield stress of 14 different water-bentonite suspensions measured using both the direct and the indirect methods. In order to obtain a wide range of yield stress values, two different types and two concentrations of bentonite at various pH were tested. Rheological data were obtained using a rotational speed viscometer and a yield stress vane measuring device. Measured vane yield stress values ranged from 5 Pa to 83 Pa. Rheological data collected with the rotating viscometer were fitted using various conventional techniques (interpolation, linear and non-linear regression analysis) as well as using a golden section yield stress search methodology based on Herschel-Bulkley model, developed in house. The vane instrument measures directly the yield stress of the suspensions and requires no further data handling. A comparison of the measured values of the yield stress with the direct and the indirect method is then made for the water-bentonite samples. Not very large differences are observed among different techniques and the variations are discussed. Similar data from literature are also analyzed and the comparison shows that differences on the various estimation methods are much larger than the differences observed in this study.